Head and neck squamous cell carcinoma in HIV patients. Issue 2 (27th April 2023) - Rampinelli, Vittorio; Gennarini, Francesca; Borsetto, Daniele; Piazza, Cesare
Abstract : Purpose of review: The introduction of antiretroviral therapy has significantly impacted the incidence of head and neck squamous cell carcinoma (HNSCC) in people living with HIV (PLWH). This manuscript aims to give an overview of the evidence in the literature about this population. Recent findings: PLWH have an increased incidence of HNSCC, with earlier age and more advanced stage at diagnosis. This epidemiologic trend may be explained by combining traditional and HIV-related risk factors. With the improvement of global health status, more patients are candidate for complex therapeutic strategies with curative intent. To date, it is still debated whether HIV-infected patients possess a profile of increased risk regarding treatment-related toxicity and survival outcomes, with the literature still lacking substantial evidence. Among the prognostic factors that can guide the clinician in selecting the most appropriate treatment strategy, age, site/subsite, stage, HIV viral load, and CD4+ T-cell count at diagnosis are the most relevant. Summary: Pathogenesis, treatment characteristics, oncologic outcomes, and prognostic factors of HNSCC in PLWH are still debated. Given the increasing incidence of HNSCC in PLWH, the need for dedicated evidence-based studies represents a significant research gap to be addressed.